Sobre Díaz Fuentes, Daniel, Andrés Hoyo Aparicio y Carlos Marichal Salinas (eds.), Orígenes de la globalización bancaria. Experiencias de España y América Latina - Blasco Martel, Yolanda (Historia Mexicana, 2020)
-